Negating the Role of Institutions in the Long Run Growth of an Oil Producing Country - Haque, Mohammad Imdadul (International Journal of Energy Economics and Policy, 2020)
The Kingdom of Saudi Arabia has a dominant oil sector. It is assumed that enormous oil revenues put a curse of poor economic growth in predominantly natural resource based economy and the country becomes a rentier state. The study attempts to estimate the relationship between economic growth, oil rents and institutional quality. The study finds a cointegrating relationship between the variables. The study argues that the country is not experiencing the phenomenon of resource curse as oil rents are not negatively impacting economic growth in the long run. Using non linear ARDL method the study reports a higher rate of growth to a positive shock in oil rents as compare to negative shocks in oil rents. This hints at the resilience of the country as the country's growth rate is less effected with the fall in oil rents. It is also assumed that mere rent seeking economies tend to have poor quality of institutions. The study finds no significant relationship between institutional quality and the rate of growth for the country. Finally, the study recommends increasing the level of economic diversification and developing the quality of institutions. Keywords: Rentier state, Resource curse, Oil rents, Institutional quality, Asymmetric relationship. JEL Classifications: Q30 O43, O53 DOI: https://doi.org/10.32479/ijeep.9870